Morpho‐Physiological Growth and Yield Responses of Two Contrasting Maize Cultivars to Cadmium Exposure. Issue 1 (27th November 2015) - Anjum, Shakeel Ahmad; Tanveer, Mohsin; Hussain, Saddam; ullah, Ehsan; Wang, Longchang; Khan, Imran; Samad, Rana Abdul; Tung, Shahbaz Atta; Anam, Madiha; Shahzad, Babar
Abstract : Increasing soil contamination by cadmium (Cd) has emerged one of the gravest threats to environmental sustainability and global food security. Maize, a major staple food, is supposed as the conspicuous source for intake of Cd by human beings. The present study investigated the morpho‐physiological growth and yield responses of two contrasting maize cultivars (Run Nong 35 and Wan Dan 13) to different Cd toxicity levels (0, 75, 150, 225, 300, and 375 μM). A considerable reduction in the growth and yield performance of both maize cultivars were noticed upon exposure to Cd stress and such a reduction governed by Cd was concentration dependent. Therefore, an increase in Cd concentration resulted in a proportional decrease in all growth (plant height, number of leaves per plant, leaf area, and ear length) and yield attributes (number of kernels per row, number of kernels per cob, and 100‐kernel weight). Osmolytes accumulation (soluble proteins, soluble sugar, and proline contents) also varied in the response to different Cd toxicity levels and maximum values for these attributes were recorded at 375 μM Cd in both cultivars. Furthermore, pronounced reduction in gas exchange attributes (photosynthesis, stomatal conductance, transpiration rate, and water use efficiency), relative water contents and chlorophyll contents were observed in Cd‐stressed plants. Cultivar variations were also apparent and Wan Dan 13 outperformed the Run Nong 35 for all studied attributes. Wan Dan 13 appeared a promising maize cultivar manifesting Cd tolerance that was related to higher osmolytes accumulation and better photosynthetic activity. Abstract : Morpho‐physiological growth and yield responses of two contrasting maize cultivars (Run Nong 35 and Wan Dan 13) to different Cd toxicity levels were investigated. An increase in the Cd concentration resulted in a proportional decrease in all growth and yield attributes. Wan Dan 13 appeared to be a promising maize cultivar manifesting Cd tolerance and higher grain yield related to higher osmolytes accumulation and better photosynthetic activity.